2014
DOI: 10.1007/s10072-014-1870-x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance and cognitive disorder: epidemiological analysis in a cohort of 263 patients

Abstract: The aim of this study was to investigate and describe frequency and characteristics of sleep disorders in a large cohort of community dwelling persons with several degrees and typologies of cognitive disorders. 236 patients (78 men and 158 women) were enrolled with different subtypes of dementia: Alzheimer's disease (AD), vascular dementia (VaD), mixed dementia, mild cognitive impairment (MCI), dementia with Lewy bodies (DLB), parkinson's disease dementia (PDD), and frontotemporal lobar degeneration (FTLD), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 44 publications
3
34
0
5
Order By: Relevance
“…30 Every type of sleep disturbance is present in each type of dementia but with significant differences; insomnia is found to be more frequent in Alzheimer's disease. 31 Consistent with previous studies, our results supported the significant correlations between insomnia and mild cognitive impairment and dementia; cognitive impairment had a higher risk of insomnia.…”
Section: Discussionsupporting
confidence: 92%
“…30 Every type of sleep disturbance is present in each type of dementia but with significant differences; insomnia is found to be more frequent in Alzheimer's disease. 31 Consistent with previous studies, our results supported the significant correlations between insomnia and mild cognitive impairment and dementia; cognitive impairment had a higher risk of insomnia.…”
Section: Discussionsupporting
confidence: 92%
“…The sleep changes observed in dementias (though similar to those reported in normal aging) are more severe than would be expected for the patient's age (Peter-Derex et al, 2015). In patients with dementia due to AD, sleep disturbances tend to occur more frequently than in the general population; it also appears early in the course of the disease Pistacchi et al, 2014;Urrestarazu and Iriarte, 2016), usually becoming more marked with progression of the disease. Studies have observed that these sleep disturbances are associated with increased memory and cognitive impairment (McCurry et al, 2000;Moran eta., 2005).…”
Section: Dementia-associated Sleep Disorderssupporting
confidence: 68%
“…There is also evidence that alterations in sleep architecture and sleep disorders may disrupt neuronal pathways that impact brain structure and function (as observed in subjects with obstructive sleep apnoea); presenting a significant risk for the development of neurodegenerative disorders and/or neurocognitive disorders (Ancoli-Israel et al, 1991;Ancoli-Israel et al, 2008;Kim et al, 2011;Kim et al, 2013). Alterations in sleep pattern, which may occur as a consequence of normal aging or neurodegenerative brain disease, has been reported to occur with increasing prevalence in individuals with dementia (Pistacchi et al, 2014;Cipriani et al, 2015). Circadian system alteration, which may manifest as disruption in the daily rhythms of physiologic parameters such as sleep, activity and hormone secretion, have also been observed as a symptom of a number of neurocognitive disorders including Alzheimer disease (Musiek, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia may lead to significant negative outcomes for individuals and society as a whole . Insomnia is associated with decreased quality of life, cognitive impairment, and increases in physical disorders, psychological disorders, and incidence of falls . Elderly with insomnia complain of fatigue, mood changes (e.g.…”
Section: Introductionmentioning
confidence: 99%